2009
DOI: 10.1007/s11250-009-9410-z
|View full text |Cite
|
Sign up to set email alerts
|

Buffel grass (Cenchrus ciliaria L.) substitution for orange pulp on intake, digestibility, and performance of hairsheep lambs

Abstract: Twenty Dorper x Pelibuey male lambs were used to evaluate the effect of substitution of forage with fresh orange pulp (FOP) in diets for fattening lambs on productive behavior, nutrient intake, apparent digestibility coefficient, and feeding costs. Lambs were divided into five groups (n = 4) and then housed in individual pens during 70 d. Treatments consisted of five levels of FOP (0, 25, 50, 75 and 100%) which substituted buffel grass hay on the base diet (40:60%, forage:concentrate). Additionally, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The values for of DFI recorded in this study were lower than those reported by Cienfuegos-Rivas et al (16), in lambs fed with rations that included dehydrated orange pulp, in which consumption was higher as the level of residue increased. Similarly, Macias-Cruz et al (14), when including up to 30% of fresh orange pulp, obtained a quadratic behavior in consumption (1.13, 1.22, 1.34 and 1.32 kg d -1 ) of diets that included 0, 15, 30 and 45% of pulp, respectively. However, the results of this study are different from those reported by Villanueva et al (5), with DFI of 1.35, 1.22, 1.07 and 0.97 kg by incorporating 15, 20, 25, and 30% of fresh orange pulp in the rations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The values for of DFI recorded in this study were lower than those reported by Cienfuegos-Rivas et al (16), in lambs fed with rations that included dehydrated orange pulp, in which consumption was higher as the level of residue increased. Similarly, Macias-Cruz et al (14), when including up to 30% of fresh orange pulp, obtained a quadratic behavior in consumption (1.13, 1.22, 1.34 and 1.32 kg d -1 ) of diets that included 0, 15, 30 and 45% of pulp, respectively. However, the results of this study are different from those reported by Villanueva et al (5), with DFI of 1.35, 1.22, 1.07 and 0.97 kg by incorporating 15, 20, 25, and 30% of fresh orange pulp in the rations.…”
Section: Discussionmentioning
confidence: 71%
“…The results obtained for the IVDMD of the rations used increased as the level of FLP increased (Figure 1), until obtaining a value of 68.1% for T 3 (20% of FLP). Macias-Cruz et al (14) reported that increasing fresh orange pulp in rations from 30 to 40%, the IVDMD improved from 80.6 to 84.2%, so it is expected than an increase in IVDMD will raise the ME level in the ration. However, Dadvar et al (13) found that IVDMD was 60.45%.…”
Section: Discussionmentioning
confidence: 99%
“…Macías-Cruz et al (2010) indicated that the DM, OM, and CP apparent digestibility and intake increased with the inclusion of citrus pulp at 75% of the diet DM. The improvements observed in the apparent digestibility of the diet may be due to the better nutrient profile and higher solubility of carbohydrates in the rumen, however, in the present study, IVDMD and IVOMD were improved with the increasing levels of DCP (linear effect P<0.01; Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Los sistemas de producción intensivos de ovinos requieren la inclusión de ingredientes energéticos y proteicos en las dietas, lo que incrementa los costos de la dieta de estos animales. Una alternativa que se ha empleado para disminuir los costos de producción en regiones tropicales, son las frutas de temporada (mango, naranja y coco) que son ricas en azúcares fermentables, ácidos orgánicos, fibra y altamente digestibles (Macías-Cruz et al, 2010). En rumiantes es necesario adicionar a las dietas un alto porcentaje de fibra, normalmente esta es suplida con el rastrojo molido de maíz, en los últimos años este se ha encarecido, por tal motivo es necesario la búsqueda de otras fuentes alternas como el aserrín de pino y el olote de maíz (Pérez-Sato et al, 2021).…”
Section: Características Físicas Do Líquido Ruminal E Das Fezes De Co...unclassified